Nation-wide analysis of the impact of Covid-19 pandemic on daily urology practice in Turkey - TANIDIR, YILÖREN (WILEY, 2021)
Objective To present a nation-wide analysis of the workload of urology departments in Turkey week-by-week during Covid-19 pandemic. Methodology The centres participating in the study were divided into three groups as tertiary referral centres, state hospitals and private practice hospitals. The number of outpatients, inpatients, daily interventions and urological surgeries were recorded prospectively between 9-March-2020 and 31-May-2020. All these variables were recorded for the same time interval of 2019 as well. The weekly change of the workload of urology during pandemic period was evaluated, also the workload of urology and the distributions of certain urological surgeries were compared between the pandemic period and the same time interval of the year 2019. Results A total of 51 centres participated in the study. The number of outpatients, inpatients, urological surgeries and daily interventions were found to be dramatically decreased by the 3rd week of pandemics in state hospitals and tertiary referral centres; however, the daily urological practice were similar in private practice hospitals throughout the pandemic period. When the workload of urology in pandemic period and the same time interval of the year 2019 were compared, a huge decrease was observed in all variables during pandemic period. However, temporary measures like ureteral stenting, nephrostomy placement and percutaneous cystostomy have been found to increase during Covid-19 pandemic compared with normal life. Conclusions Covid-19 pandemic significantly affected the routine daily urological practice likewise other subspecialties and priority was given to emergent and non-deferrable surgeries by urologists in concordance with published clinical guidelines.